Health Expenditure Concentration and Characteristics of High-Cost Enrollees in CHIP - Bisakha Sen PhD; Justin Blackburn PhD; Monica S. Aswani MSPH; Michael A. Morrisey PhD; David J. Becker PhD; Meredith L. Kilgore PhD; Cathy Caldwell MPH; Chris Sellers MPH; Nir Menachemi PhD (SAGE Publishing, 2016)
Devising effective cost-containment strategies in public insurance programs requires understanding the distribution of health care spending and characteristics of high-cost enrollees. The aim was to characterize high-cost enrollees in a state's public insurance program and determine whether expenditure inequality changes over time, or with changes in cost-sharing policies or program eligibility. We use 1999-2011 claims and enrollment data from the Alabama Children's Health Insurance Program, ALL Kids. All children enrolled in ALL Kids were included in our study, including multiple years of enrollment (N = 1,031,600 enrollee-months). We examine the distribution of costs over time, whether this distribution changes after increases in cost sharing and expanded eligibility, patient characteristics that predict high-cost status, and examine health services used by high-cost children to identify what is preventable. The top 10% (1%) of enrollees account for about 65.5% (24.7%) of total program costs. Inpatient and outpatient costs are the largest components of costs incurred by high-cost utilizers. Non-urgent emergency department costs are a relatively small portion. Average expenditure increases over time, particularly after expanded eligibility, and the share of costs incurred by the top 10% and 1% increases slightly. Multivariable logistic regression results indicate that infants and older teens, Caucasian children, and those with chronic conditions are more likely to be high-cost utilizers. Increased cost sharing does not reduce cost concentration or average expenditure among high-cost utilizers. These findings suggest that identifying and targeting potentially preventable costs among high-cost utilizers are called for to help reduce costs in public insurance programs.